A Comparison of Spatial Designs for Field Variety Trials. (14th July 2013) - Williams, E. R.; Piepho, H. P.
Summary: Experimental designs can be constructed to be efficient in the presence of spatial correlation. Available construction methods include those based on autoregressive and linear variance models. This paper investigates spatial designs across a range of assumed autoregressive structures. Results show that when the spatial component is low relative to the independent error term, efficient spatial designs can be constructed without having to specify parameters for the spatial structure.